Sistem Smarthome Menggunakan Aplikasi Smartphone Android Berbasis Mikrokontroller Melalui Bluetooth - Arief - Budi Laksono (Universitas Islam Lamongan, 2019)
The house is a place to take refuge, gather with family so that everyone must have a dream to have a safe and comfortable home. Now, where technological developments are very rapid, technology plays a role in building dream homes that increase the comfort of residents. The purpose of the research is to make the Smarthome system use an Android application based on the Atmega 328 microcontroller via Bluetooth.In this study the qualitative method was carried out by conducting some research, research, measurement, and conducting several experiments with Bluetooth and Android modules. The results of this study can turn on and turn off the home lights remotely through a bluetooth module with a range of 10 meters which is controlled by an android application. So that the tool can make it easier for residents of the house to control remote lights.